Teacher training: literature and inventive memory in the construction of narratives about teacher training - Cláudia Bechara Fröhlich; Simone Moschen (Arizona State University, 2012)
This article starts from a reflection about Reading-Writing Teacher's Club's project, developed in the cities of Dois Irmãos and Morro Reuter, Rio Grande do Sul, Brazil. It is an ongoing training for elementary schools teachers in which the fictional tale was built as a text for study. Our aim was to map how the shared readings took place in this work and the effects of this project on the participants' continuous training. For both, an Edge Diaries where produced in each meeting of the Club. This is a narrative about how the tale words had been worked by the participants' speech. The Edge Diaries reflection was supported by the theoretical contributions of Freud, Lacan and Barthes. It was found that the reading in the company favored the creative writing of the participants. The study also highlighted the establishment of a link between the tale signifiers and the memory fragments of the readers, which resulted in a construction of a narrative which sews the professor's personal history to their own teaching practice. While they read stories and write narratives the professors weave the plot of what we called education tale.